2020
DOI: 10.22454/fammed.2020.257274
|View full text |Cite
|
Sign up to set email alerts
|

A Curriculum to Increase Resident Scholarly Activity

Abstract: Background and Objectives: Scholarly activity (SA) is an Accreditation Council of Graduate Medical Education (ACGME) requirement for family medicine residents. Engaging residents in scholarly activity can be challenging. Naval Hospital Jacksonville Family Medicine Residency (NHJ) pioneered a curriculum that led to a dramatic, sustained increase in resident SA. We sought to implement the curriculum in other family medicine residency programs. Methods: The curriculum was implemented at two additional family medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
0
8
1
Order By: Relevance
“…This is one of only a few studies that report a positive association between a new scholarship curriculum and confidence in scholarly skills, 16,17 particularly those skills emphasized by the curriculum. 18,19 Unlike other programs, 4,8 we identified no increase in writing manuscripts, but did observe increases in abstract submissions, possibly paving the way for later publication. Strong research mentorship may be the missing ingredient for increasing manuscript output, 4,9 however, increased participation and interest are also important intrinsic motivations for scholarship.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…This is one of only a few studies that report a positive association between a new scholarship curriculum and confidence in scholarly skills, 16,17 particularly those skills emphasized by the curriculum. 18,19 Unlike other programs, 4,8 we identified no increase in writing manuscripts, but did observe increases in abstract submissions, possibly paving the way for later publication. Strong research mentorship may be the missing ingredient for increasing manuscript output, 4,9 however, increased participation and interest are also important intrinsic motivations for scholarship.…”
Section: Discussioncontrasting
confidence: 68%
“…In conclusion, this study provides evidence that resident interest, confidence and participation in scholarly activity may be influenced by a scholarship curriculum that is longitudinal, driven by residents, and able to incorporate resident-identified topics in health research. 18 As resident scholarly pursuits increase, our findings highlight the need for faculty to enhance their own scholarly portfolios. To that end, endeavors at the national level to address faculty scholarship and research training pipelines are encouraging.…”
Section: Brief Reportsmentioning
confidence: 82%
“…Notably, our journal café model is unique because it is independently run by residents and complements the residency program’s traditional journal club rather than the implementation of supplementary curriculum and modification of journal club activities reported by some residency specialties in the literature. 1214…”
Section: Discussionmentioning
confidence: 99%
“…Notably, our journal café model is unique because it is independently run by residents and complements the residency program's traditional journal club rather than the implementation of supplementary curriculum and modification of journal club activities reported by some residency specialties in the literature. [12][13][14] Internal medicine residents interested in pursuing subspecialty fellowship after residency were more likely to join the journal café, which is unsurprising because studies have shown that a high number of research publications and involvement in academic scholarship during residency is associated with success in the fellowship match. 16,17 Similarly, most residents apply to fellowship programs at the end of PGY-2 and the beginning of PGY-3, which likely explains the predominance of PGY-2 residents in the journal café membership.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in South Africa quality metrics are used to monitor indicators such as progress through the degree, quality of dissertations, skills for communicating research, quality of the research training environment, research impact, completion, attrition and career placement (3). Curriculum initiatives such as having faculty research coordinators, research and conference tracking systems, and resident research coordinator are systems that can improve residency scholarly productivity both during residency and after (31).…”
Section: Research and Dissertation Quality Assessment Mechanismsmentioning
confidence: 99%